L(3)mbt and the LINT complex safeguard cellular identity in the Drosophila ovary - Coux, Rémi-Xavier (Development, 2018)
Maintenance of cellular identity is essential for tissue development and homeostasis. At the molecular level, cell identity is determined by the coordinated activation and repression of defined sets of genes. The tumor suppressor L(3)mbt has been shown to secure cellular identity in Drosophila larval brains by repressing germline-specific genes. Here, we interrogate the temporal and spatial requirements for L(3)mbt in the Drosophila ovary, and show that it safeguards the integrity of both somatic and germline tissues. l(3)mbt mutant ovaries exhibit multiple developmental defects, which we find to be largely caused by the inappropriate expression of a single gene, nanos, a key regulator of germline fate, in the somatic ovarian cells. In the female germline, we find that L(3)mbt represses testis-specific and neuronal genes. At the molecular level, we show that L(3)mbt function in the ovary is mediated through its co-factor Lint-1 but independently of the dREAM complex. Together, our work uncovers a more complex role for L(3)mbt than previously understood and demonstrates that L(3)mbt secures tissue identity by preventing the simultaneous expression of original identity markers and tissue-specific misexpression signatures.